2019
DOI: 10.3390/ani9110988
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Detection of Encephalitozoon cuniculi in Ocular Structures of Immunocompetent Rabbits

Abstract: Simple SummaryEncephalitozoonosis is a common infectious disease widely spread among rabbits. Its causative agent, Encephalitozoon cuniculi, is considered to be transmissible to humans. In rabbits, clinical signs include discoordination, head tilt, excessive water intake, excessive urination and cataracts. This study investigates, for the first time, whether the E. cuniculi organism can be detected in ocular structures in healthy adult rabbits after experimental oral infection using immunohistochemistry—detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, we have focused on the assessment of renal pathology in wild rabbits, and with respect to potential E. cuniculi infection; we did not perform PCR, immunohistochemistry, corresponding serology or histology of other potentially affected organs, such as the brain or ocular tissues. 16,17 In spite of these limitations, our findings add weight to the assertion that E. cuniculi may not currently be highly prevalent in wild rabbits in the UK, and our data raise interesting questions regarding the apparent discrepancy between the prevalence of E. cuniculi in wild and domestic UK rabbits. 4,5,8,18 It is possible that other wild animals, such as wild rodents and foxes, may constitute more notable reservoirs of infection and may have the potential to infect domestic pet rabbits.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Furthermore, we have focused on the assessment of renal pathology in wild rabbits, and with respect to potential E. cuniculi infection; we did not perform PCR, immunohistochemistry, corresponding serology or histology of other potentially affected organs, such as the brain or ocular tissues. 16,17 In spite of these limitations, our findings add weight to the assertion that E. cuniculi may not currently be highly prevalent in wild rabbits in the UK, and our data raise interesting questions regarding the apparent discrepancy between the prevalence of E. cuniculi in wild and domestic UK rabbits. 4,5,8,18 It is possible that other wild animals, such as wild rodents and foxes, may constitute more notable reservoirs of infection and may have the potential to infect domestic pet rabbits.…”
Section: Discussionmentioning
confidence: 50%
“…Seasonality of sampling was also unequal. Furthermore, we have focused on the assessment of renal pathology in wild rabbits, and with respect to potential E. cuniculi infection; we did not perform PCR, immunohistochemistry, corresponding serology or histology of other potentially affected organs, such as the brain or ocular tissues 16,17 …”
Section: Discussionmentioning
confidence: 99%
“…The disease is widespread among laboratory, farm, and pet rabbits. According to some studies, serological testing shows high seroprevalence rates (35-68%) across several countries [3,7,8]. These results suggest that E. cuniculi infection is ubiquitous in rabbits [9,10].…”
Section: Introductionmentioning
confidence: 92%
“…5 In veterinary ophthalmology, E cuniculi is predominantly known as a cause of cataracts and phacoclastic uveitis in rabbits; 6,7 after transplacental transmission, spores are speculated to enter the lens via the lenticular blood supply while it is still present. 8 However, a recent study with immunohistochemical evidence of intralenticular E cuniculi after oral infection in 4-month-old, immunocompetent, specific pathogen-free rabbits 9 suggested that alternative mechanisms for lens infections are possible. Reports of ocular involvement in other species are limited and include cataract and uveitis in a snow leopard in France, 10 cataract, uveitis and chorioretinal lesions in dogs in Europe, 11 keratitis and uveitis in an American cat, 12 polyarteritis nodosa and cataract in a blue fox, 13 cataract and neurologic lesions in mink in Norway 14 and keratoconjunctivitis in an American cockatoo.…”
Section: Introductionmentioning
confidence: 99%